Immediate efficacy of auricular acupuncture combined with active exercise in the treatment of acute lumbar sprains in 10 minutes: Protocol of a randomized controlled trial. - Xin Tang; Qifu Li; Gaoyangzi Huang; Xianmei Pei; Ziwen Chen; Ya Huang; Siwen Zhao; Taipin Guo; Zili Liu (PLoS ONE)
Background Acute lumbar sprain (ALS) is common musculoskeletal disorder characterized by severe low back pain and activity limitation, which significantly impacts the patient's work and life. Immediate relief of pain and restoration of mobility in a short period of time are the main needs of patients when they visit the clinic. This study aims to evaluate the immediate efficacy of this combined treatment for ALS within 10 minutes. Methods This is a single-center, prospective, randomized clinical trial. 128 eligible patients with ALS will be randomly allocated in a 1:1 ratio to either the auricular acupuncture (AA) group or the sham auricular acupuncture (SAA) group. All patients will receive a single 10-minute treatment. The primary outcome will be the change in pain intensity after 10 minutes of treatment. The secondary outcomes include changes in pain intensity at other time points (2, 5 minutes), changes in lumbar range of motion (ROM) at different time points, blinded assessment, treatment effect expectancy scale evaluation, and treatment satisfaction scale evaluation. All participants will be included in the analysis according to the intention-to-treat principle. Discussion This is the first randomized controlled trial to assess the immediate efficacy of AA combined with active exercise for ALS. The findings of this study are expected to provide a simple and rapid treatment for ALS in clinical. Trial registration Chinese Clinical Trial Registry ChiCTR2400083740. Registered 30 April 2024.